Pro Kontra Kader Politik Perempuan Di Indonesia: (Studi Komparatif Pemikiran Yusuf Al-Qardhawi) - Dewi, Sri Intan Kumala; Junaidi, Junaidi (Jayapangus Press, 2024)
The study aims to analyze the pros and cons of women's political cadres in Indonesia by examining Yusuf Al-Qardhawi's thinking as a comparative study. Since ancient times, women have been involved in politics. This is not a new phenomenon; for instance, there are differences of opinion among scholars about the role of women in politics, particularly on the controversial topic of Muslim women's leadership. In addition to other gender equality issues, the debate over the 30-percent quota for women in politics continues to this day. The study compares Al-Qardhawi's thinking with the political reality of Indonesian women using qualitative methods and literary study approaches. The findings show that a moderate and inclusive view came from Yusuf Al-Qardhawi, who stressed the importance of education and women's empowerment as a measure to ensure wider and more effective participation in politics. In his diverse viewpoints and assessments of women's role in government issues, he believes that the above assumptions are not limited to the text, but should also take into account specific circumstances. He believes that man is amukallaf, meaning that he is obligated to love God, observe religion, fulfill commitments, engage in both good and evil actions, and have a purpose. Al-Qardhawi establishes a number of unique conditions that allow women to assume social roles like judges. He believes that the position does not conflict with social interests; instead, women are required to participate in social activities. The research is expected to provide policymakers and society with new insights into the pro and contra dynamics of women's political cadres in Indonesia, as well as theoretical foundations for the development of more inclusive and fair policies for women in politics.